2015
DOI: 10.1094/cchem-11-14-0232-r
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Infrared and Conventional Drying Methods on Physicochemical Characteristics of Stored White Rice

Abstract: 26The objective of this study was to investigate the effect of infrared (IR) drying 27 followed by tempering and natural cooling on the change of physicochemical 28 characteristics of white rice during up to 10 months of storage. The physicochemical 29 characteristics of IR dried rice were also compared with that of conventionally dried rice. 30It took only 58 s to heat the rough rice from room temperature to 60 °C using IR and 2.17 31 percentage points of moisture was removed. After 4 months of storage, the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…The protein complexation limits the leaching of solids during cooking and increases hardness after cooking (Derycke et al, ). These conditions combined undesired changes in milling and color parameters along with increased grain hardness, which is also an undesired sensory attribute (Ding, Khir, Pan, Zhang, et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The protein complexation limits the leaching of solids during cooking and increases hardness after cooking (Derycke et al, ). These conditions combined undesired changes in milling and color parameters along with increased grain hardness, which is also an undesired sensory attribute (Ding, Khir, Pan, Zhang, et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The protein complexation limits the leaching of solids during cooking and increases hardness after cooking (Derycke et al, 2005). These conditions combined undesired changes in milling and color parameters along with increased grain hardness, which is also an undesired sensory attribute (Ding, Khir, Pan, Zhang, et al, 2015). Bualuang et al (2012) studied the drying of parboiled rice with IR (1,000 to 1,500 W) and hot air with a temperature range of 60 to 100 C. These authors reported an increase in the hardness of the rice grains according to the increase of the drying temperature.…”
Section: Cooking Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The taste properties of milled rice can be indicated by TPA indices. Hardness is one of the most representative sensory properties of rice; a lower hardness is important for the sensory experience of consuming rice (Ding et al, 2015). As seen in Table 1, the drying method and the intermittent ratio (d) both had significant effects on the hardness of cooked paddy rice (P < 0.05).…”
Section: Effects Of Drying Methods and The Intermittent Ratio On Tpa mentioning
confidence: 99%
“…HP dryers are economical and efficient and have been proven to ensure product quality, especially for food and agriculture products (Goh et al, 2011). Infrared (IR) drying also provides significant advantages over conventional drying methods, including reductions in drying time and quality losses, uniform drying, an absence of solute migration in food material, a compact size of the equipment and significant energy savings (Khir et al, 2011;Ding et al, 2015).…”
Section: Introductionmentioning
confidence: 99%